Cyproideidae - Azman, B. A. R. (Zootaxa, 2009)
Two new species of cyproideid amphipods, Cyproidea cobia, sp. nov. and Narapheonoides lowryi, sp. nov., are described from the Great Barrier Reef. Cyproidea cobia, sp. nov., is characterized by gnathopod 1 having a rectolinear basis and gnathopod 2 ischium posterior process not developed. Narapheonoides lowryi, sp. nov., differs from its congeners in that the basis in both pereopods 6 and 7 has a posterodistal flange and the pereopod 6 basis is broader. With the recently described Gbroidea dingaalana Lowry & Azman, 2008, collected from Lizard Island, this study brings the number of known cyproideid amphipods from the Great Barrier Reef to three species.